Funciones de la familia - Saldaa Bernal, Cynthia Katya (2019)
The work of professional sufficiency was entitled Family Functions, whose development of the_x000D_ learning session has been based on bibliographic references and other sources of consultation, as_x000D_ well as with the application of knowledge acquired in the academic years of my professional training._x000D_ My conclusions summarize that: the family is the most important thing that each human being has,_x000D_ the best that GOD has given us, and above all the kindness and understanding that we find in her, of_x000D_ course when we know how to take care of her and respect first and foremost because Sometimes we_x000D_ think that the family we have is not adequate, that they do not know how to understand us but you_x000D_ are wrong because the family we have is the best of all and that the basis that a family constitutes a_x000D_ couple and the children they have procreated , we will realize that it is within it, where children should_x000D_ learn the principles and values that will guide their future behavior and those that will help them_x000D_ choose between good and evil once they grow up and that each family is different , some more_x000D_ numerous than others, with different customs and traditions, but finally we all have a_x000D_ The competence that was developed in this class corresponds to "Build Your Identity", in which_x000D_ students must be recognized as a member of a specific sociocultural community and have the sense_x000D_ of permanence to their family._x000D_ The didactic processes allow to better organize the students' learning, organizing their knowledge in_x000D_ an orderly manner. The interaction between the teacher and the student allows an integration_x000D_ between the whole classroom, the images being recommended.